Over-age children in Colombia: analysis of educational policies and inclusive processes in the classroom - Aravena Domich, Marcela (2025)
This essay was carried out in the form of a documentary review of research and articles that provide theoretical elements, data and legal foundations about the phenomenon of school overage as a situation of educational inclusion in schools in Colombia and some countries in the region. Its objective was to understand the educational reality that underlies the condition of school age, as a process of educational inclusion. Extra-age is understood to be the situation where students have an age range greater than the average of other students in the same grade. This problem is caused by diverse causes: social, family and academic, and has an impact on the personal, professional and family development of educational subjects. That is why government entities and social organizations have proposed policies and action plans to minimize the negative repercussions on individual and social development. In conclusion, school age generates situations of exclusion and school segregation. Likewise, the care policies implemented have been managing to improve the access and coverage rates of students, but there is still work to be done on strategies for permanence and care. relevant pedagogical; because teachers and teaching managers do not have sufficient professional and personal training to manage and implement a flexible and relevant curriculum that contributes to the inclusion needs of these students.